Answer:
c
Step-by-step explanation:
Since both equations express y in terms of x we can equate the right sides
3x + 5 = - x + 3 ( add x to both sides )
4x + 5 = 3 ( subtract 5 from both sides )
4x = - 2 ( divide both sides by 4 )
x = - 0.5
substitute x = - 0.5 in either of the 2 equations
using y = - x + 3 then y = 0.5 + 3 = 3.5
solution is (- 0.5, 3.5 ) → c
Answer:
15 hip hop performances
12 ballet performances
Step-by-step explanation:
5:4 (multiply by 3)
15:12
G(x) = 3x + 1, evaluate g(-2).
Simply plug in (- 3) in g(x)
g(-2) = 3(-2) + 1
g(-2) = - 6 +1
g(-2) = - 5
Answer:
C on Edge 2020
Step-by-step explanation:
The graph where the 60 degree angle is touching the y axis and air is above ground